DEVELOPMENT OF SMART BOARD LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS II MATHEMATICS SUBJECTS AT BUNGA TANJONG PRIVATE PRIVATE PRIMARY SCHOOL - Purba, Alda Miranda; Sutarini, Sutarini; Destini, Rita; Barus, Ulian (Media Inovasi Pendidikan dan Publikasi, 2024)
The objectives of this research were to develop a suitable Interactive Whiteboard for teaching mathematics on the topics of time and duration for second-grade students, to assess students' responses to the developed media, and to evaluate the improvement in students' learning outcomes using this media. The research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The results of material validation in the first phase yielded an 89% rating, indicating it was suitable. In the second phase, it received a 95% rating, indicating it was very suitable. The media content validation results in the first phase yielded a 55% rating, indicating it was fairly suitable, and in the second phase, it received a 93% rating, indicating it was very suitable. Teacher response to the developed media was 83%, and student response, based on questionnaires distributed to 24 students, was 77%. There was an increase in student learning outcomes using the Interactive Whiteboard for the mathematics subject on time and duration.